Work-based social interactions, perceived stress, and workload incongruence as antecedents of Athletic Trainer Burnout - DeFreese, J. D.; Mihalik, J. P. (Journal of Athletic Training, 2016)
Context: Burnout is an important psychological health concern for working professionals. Understanding how psychological stress and markers of workload contribute to athletic trainers' (ATs') perceptions of burnout is highly valuable. Both positive (social support) and negative social interactions should be considered when examining relationships among markers of ATs' health and wellbeing.